(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2010)
The Lower Pliocene succession recovered at ODP Hole 975B (Balearic Basin, western Mediterranean) displays a sudden increase in sedimentation rate, in disagreement with the lithological homogeneity that characterizes the succession. The present study, consisting of a high resolution stratigraphic analysis, demonstrates that the succession is affected by repetition. The section has been astrochronologically constrained through integration of detailed biostratigraphy and cyclostratigraphy, which permitted a precise evaluation of the length and duration of the duplicated interval. This result demonstrates the efficacy of integrated stratigraphy in solving wide-range geological problems.